2008
DOI: 10.1371/journal.pone.0002047
|View full text |Cite
|
Sign up to set email alerts
|

NF-Y Dependent Epigenetic Modifications Discriminate between Proliferating and Postmitotic Tissue

Abstract: The regulation of gene transcription requires posttranslational modifications of histones that, in concert with chromatin remodeling factors, shape the structure of chromatin. It is currently under intense investigation how this structure is modulated, in particular in the context of proliferation and differentiation. Compelling evidence suggests that the transcription factor NF-Y acts as a master regulator of cell cycle progression, activating the transcription of many cell cycle regulatory genes. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 58 publications
(72 reference statements)
2
58
0
Order By: Relevance
“…Reduction of NF-YA expression has been reported in IMR-90 fibroblasts after serum deprivation (Chang et al, 1994) and in human monocytes (Marziali et al, 1997). The NF-YA protein is not expressed in terminally differentiated C2C12 muscle cells and adult skeletal muscle tissues (Farina et al, 1999;Gurtner et al, 2003Gurtner et al, , 2008. These observations show that levels of NF-YA dictate the function of the NF-Y complex.…”
mentioning
confidence: 59%
See 4 more Smart Citations
“…Reduction of NF-YA expression has been reported in IMR-90 fibroblasts after serum deprivation (Chang et al, 1994) and in human monocytes (Marziali et al, 1997). The NF-YA protein is not expressed in terminally differentiated C2C12 muscle cells and adult skeletal muscle tissues (Farina et al, 1999;Gurtner et al, 2003Gurtner et al, , 2008. These observations show that levels of NF-YA dictate the function of the NF-Y complex.…”
mentioning
confidence: 59%
“…After treatment, the NF-YA protein accumulated both in the cytoplasm and in the nucleus, whereas the protein levels of NF-YB and -YC were only slightly modulated. We have previously demonstrated that in terminally differentiated C2C12 muscle cells, myotubes, NF-YA expression is abrogated (Farina et al, 1999;Gurtner et al, 2003Gurtner et al, , 2008. Thus, we asked whether regulation of NF-YA expression occurs at posttranslational level in this cell system.…”
Section: The Proteasome Pathway Regulates Nf-ya Expressionmentioning
confidence: 94%
See 3 more Smart Citations